Comparison of short‐course antibiotic therapy of 6 or less days with a longer treatment in patients with cholangitis after liver transplantation. Issue 4 (6th June 2022) - Ferstl, Philip G.; Queck, Alexander; Bremer, Katharina; Filmann, Natalie; Weiler, Nina; Welker, Martin‐W.; Waidmann, Oliver; Knabe, Mate; Bechstein, Wolf O.; Hogardt, Michael; Kempf, Volkhard A. J.; Zeuzem, Stefan; et al.
Abstract: Objectives: Stenosis of the biliary anastomosis predisposes liver graft recipients to bacterial cholangitis. Antibiotic therapy (AT) is performed according to individual clinical judgment, but duration of AT remains unclear. Methods: All liver graft recipients with acute cholangitis according to the Tokyo criteria grade 1 and 2 after endoscopic retrograde cholangiography (ERC) were included. Outcome of patients treated with short AT (<7 days) was compared to long AT (>6 days). Recurrent cholangitis (RC) within 28 days was the primary end point. Results: In total, 30 patients were included with a median of 313 (range 34–9849) days after liver transplantation until first proven cholangitis. Among 62 cases in total, 51/62 (82%) were graded as Tokyo‐1 and 11/62 (18%) as Tokyo‐2. Overall median duration of AT was 6 days (1–14) with 36 cases (58%) receiving short AT and 26 (42%) receiving long AT. RC was observed in 10 (16%) cases, without significant difference in occurrence of RC in short versus long AT cases. CRP and bilirubin were significantly higher in patients with long AT, while low serum albumin and low platelets were associated with risk of RC. Conclusion: A shorter antibiotic course than 7 days shows good results in selected, ERC‐treated patients for post‐transplantation biliary strictures.